Exploring the Nexus of Company Size, Debt Levels, Liquidity, and Profitability: Implications for Firm Value in the Indonesian Manufacturing Sector - Okadasa, J’Hazkel Victora; Chabachib, Mochammad (Diponegoro Journal of Management, 2024)
This study investigates the relationship between company size, debt levels, liquidity, profitability, and the value of companies in the Indonesian manufacturing sector. Using regression analysis on data from 95 manufacturing firms listed on the Indonesia Stock Exchange from 2018 to 2022, the research explores how these variables interact. Total assets, Debt-to-Equity Ratio (DER), and Cash Ratio are considered as independent variables, while Return on Investment (ROI) serves as the mediating variable, and Priceto-Book Value (PBV) as the measure of company value. The findings reveal that company size does not significantly impact company value, while debt levels and profitability positively influence it. However, liquidity, although negatively related, does not significantly affect company value. Furthermore, the study shows that company size, debt levels, and liquidity indirectly influence company value through profitability. These insights contribute to understanding the dynamics of the Indonesian manufacturing sector, providing stakeholders with valuable information for formulating effective policies and strategies in a rapidly changing business environment